RANCANG BANGUN SISTEM INFORMASI INVENTORI PADA CV. MORIA BERBASIS JAVA - Ridho Sholehurrohman Ridho; Igit Sabda Ilman; Muhaqiqin Muhaqiqin; Rahman Taufik (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2022)
—Along the development of information technology in this era, it’s increasingly familiar with the use of computer-based programs that function to support the performance of an office or company so that it can run according to the desired target. One example of the use of information technology is the management and storage of web-based inventory data because manual inventory of goods is inefficient, often losing important documents. Therefore, the author intends to conduct research on the design of information systems in CV. Moria. So, it’s hoped that this java-based application can reduce the occurrence of errors and can provide convenience in processing data in an organized and efficient manner for office inventory management. Based on the research that has been done, the office inventory information system in CV. Moria. This information system is made web-based so that it can be accessed via smartphones or computers. This system was also created to make it easier to control inventory stock. The information generated from this information system is available stock data, incoming goods transaction data, and goods transaction data used.